Essays in ecumenical theology - Noble, Ivana, (Studies in Reformed Theology, 2018)
In the first volume of Essays in Ecumenical Theology Ivana Noble depicts differences between what she calls a sectarian outlook and one which engages in the search for common roots, dialogical relationships and shared mission in a world that has largely become post-Christian, but often also post-secular. Drawing on both Western and Orthodox scholarship, and expressing her own positions, Noble sketches what ecumenical theology is, how it is linked to spirituality, the methods it uses, how it developed during the twentieth century, and the challenges it faces. Specific studies deal with controversial interpretations of Jan Hus, Catholic Modernism, the problematic heritage of the totalitarian regimes, and responses to the current humanitarian crisis.